Effectiveness of Red Guava Leaf Ethanol Extract (Psidium guajava L.) on Increasing Hemoglobin Levels in Female White Rats (Rattus novergicus) - Yuziani; Fadhilah, Siti Ghina; Akbar, Teuku Ilhami Surya (Universitas Ahmad Dahlan, 2025)
Hemoglobin is the protein found in red blood cells that has the task of delivering oxygen to the lungs. When the hemoglobin level degrades, it can cause symptoms of anemia. Guava fruit is often used by people in traditional medicine to increase hemoglobin levels. The average person only uses the fruit because it contains flavonoids. However, generally flavonoid compounds are also contained in guava leaves. The purpose of this study is to identify the effects of extracted from guava leaves (Psidium guajava L.) on anemic hemoglobin levels of female wistar strains. The study used a laboratory experimental design with pretest and post-test group design, purposive sampling technique. The sample in this study was 30 female wistar strains divided into 5 groups, namely negative control without treatment, positive control was given sangobion to rats with anemia, and treatment groups I, II, III were given guava leaf extract at doses of 100 mg/KgBb, 250 mg/KgBb and 500 mg/KgBb to rats with anemia. Increased hemoglobin levels of guava leaves (Psidium guajava L.) respectively 13.56 gr/dl, 15.56 gr/dl dl, and 16.85 gr/dl. The most influential guava leaf extract is treatment group 3 with a dose of 500mg/kgBB and in post hoc analysis using LSD shows a significant difference between guava leaf extract at a dose of 100 mg/KgBb, 250 mg/KgBb and 500 mg/KgBb (p-value = 0.0000) in increasing hemoglobin levels